Film structures of poly(amido amine) dendrimers with an azacrown core and long alkyl chain spacers on water or Ag nanoparticle suspension - Ujihara, Masaki (Langmuir : the ACS journal of surfaces and colloids, 2005)
Newly designed poly(amido amine) dendrimers, which have an azacrown core, hexyl spacers, and methyl ester terminals (aza-C6-PAMAM dendrimer), were spread at the air-water and air-silver nanoparticle suspension interfaces, and their film structures were examined by surface pressure-area (pi-A) and surface potential-area (DeltaV-A) isotherms and epifluorescence microscopy. It was revealed that generation (G) 1.5 aza-C6-PAMAM dendrimer on a water subphase formed homogeneous film with face-on configuration, and this configuration was maintained during compression. On the other hand, a G2.5 dendrimer film on the air-water interface took initially homogeneous and face-on configuration that was followed by the conformational change during compression. Using a silver nanoparticle suspension as subphase, G1.5 film was significantly reinforced, and the partial collapse (cracks) in the film appeared as network texture. For a G2.5 dendrimer film, the pi-A and DeltaV-A isotherm properties were similar to that on the water subphase except for the collapsed film; small spots instead of cracks were formed under the film after collapse. These effects of the silver nanoparticle may be due to the formation of a dendrimer/silver nanoparticle composite. The formation process of the nanocomposite film was verified by UV-vis spectroscopy. For the G1.5 dendrimer, silver clusters and nanoparticles adsorbed to the dendrimer film after spreading and formed a small amount of aggregates. During compression, the aggregation proceeded even at low surface pressure. For the G2.5 dendrimer, a dendrimer/nanoparticle composite was also formed after spreading. However, with the initial compression, the absorption bands of clusters, nanoparticles, and aggregate increased together. Upon further compression, while the bands of cluster and nanoparticles decreased, the bands of aggregate still increased. These results suggest that the G2.5 dendrimer covered the cluster and nanoparticles more efficiently than the G1.5 dendrimer did because of the larger molecular size